2012
DOI: 10.1097/mnm.0b013e32834e306a
|View full text |Cite
|
Sign up to set email alerts
|

Low versus high radioiodine dose in postoperative ablation of residual thyroid tissue in patients with differentiated thyroid carcinoma

Abstract: The higher dose of I-131 (3700 MBq) resulted in successful ablation more often than the low dose (1110 MBq).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 29 publications
1
44
1
8
Order By: Relevance
“…Particularly, 2 large multicentre randomised trials [3,4] and 1 meta-analysis [5] have shown that low-dose radioiodine (1.1 GBq) is as effective as a high-dose (3.7 GBq) in ablating thyroid remnant in the low and intermediate risk patients. However, some series [3,4,8,9] have reported variable success rates (ranging between 39 and 98%) using a low-dose radioiodine in low/intermediate risk. This can be explained by the variability of inclusion criteria and of success ablation definition.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, 2 large multicentre randomised trials [3,4] and 1 meta-analysis [5] have shown that low-dose radioiodine (1.1 GBq) is as effective as a high-dose (3.7 GBq) in ablating thyroid remnant in the low and intermediate risk patients. However, some series [3,4,8,9] have reported variable success rates (ranging between 39 and 98%) using a low-dose radioiodine in low/intermediate risk. This can be explained by the variability of inclusion criteria and of success ablation definition.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies have shown that I-131 activity is not correlated with ablation success, some authors still recommend higher I-131 activities, while others recommend lower activities for effective ablation [10][11][12][13][14]. Similarly, in patients with ablation failure, additional uncertainties pertain to the optimal second ablation activity and the optimal combination of activities used for the first and second ablation, especially when the potential risks of treatment must be balanced against treatment success [9,[11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Following a single application of I-131, approximately 8-40% of patients require an additional application (re-ablation) due to ablation failure. Ablation activities for first and second ablation range from low (1110 MBq [30mCi]) to high (≥3700 MBq [100mCi]) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, expression of TSHR has been shown to correlate with the degree of iodine trapping (Edmonds et al 1977), and with efficacy of ablation (Fallahi et al et al 2012). Further, both positive and negative regulation of NIS mRNA in response to TSHR stimulation has been demonstrated in human thyroid cells (Saito et al 1997, Bruno et al 2005.…”
Section: Current Therapeutic Targeting Of Tshr In Dtcmentioning
confidence: 98%